Obesity - a risk factor of renal pathology in patients with type 2 diabetes mellitus - Svetlana Alekseevna Savel'eva (Endocrinology Research Centre, 2010)
Aim. To study association between obesity and renal pathology in patients with type 2 diabetes mellitus (DM2). Materials and methods. The study included 106 patients with CD2 (41 men and 65 women) of mean age 60.0?7.0 years. Exclusion criteria wereduration of DM2 less than 5 years and manifest diabetic nephropathy (DN) (glomerular filtraton rate (GFR) below 60 ml/min/m2, albuminuria over2 g/24 hr). Anthropometric parameters measured included body mass index (BMI). Serum creatinine, uric acid, lipid spectrum, hormones of adiposetissue (leptin and adiponectin) were determined. Severity of renal pathology was estimated from GF and albumin excretion in urine. The patients were categorized into 2 groups: with obesity (BMI>=30 kg/m2) and without it (BMI